Sorting Nexin1 negatively modulates phosphate uptake by facilitating Phosphate Transporter1;1 degradation in Arabidopsis. (30th April 2022) - Zhang, Yu; Wang, Lin‐Feng; Han, Shu‐Yue; Ren, Feng; Liu, Wen‐Cheng
SUMMARY: High‐affinity phosphate (Pi) transporters (PHTs) PHT1;1 and PHT1;4 are necessary for plant root Pi uptake especially under Pi‐deficient conditions, but how their protein stability is modulated remains elusive. Here, we identified a Ttransfer DNA insertion mutant of Sorting Nexin1 ( SNX1 ), which had more Pi content and less anthocyanin accumulation than the wild type under deficient Pi. By contrast, the snx1‐2 mutant displayed higher sensitivity to exogenous arsenate in terms of seed germination and root elongation, revealing higher Pi uptake rates. Further study showed that SNX1 could co‐localize and interact with PHT1;1 and PHT1;4 in vesicles and at the plasma membrane. Genetic analysis showed that increased Pi content in the snx1‐2 mutant under low Pi conditions could be extensively compromised by mutating PHT1;1 in the double mutant snx1‐2 pht1;1, revealing that SNX1 is epistatic to PHT1;1. In addition, SNX1 negatively controls PHT1;1 protein stability; therefore, PHT1;1 protein abundance in the plasma membrane was increased in the snx1‐2 mutant compared with the wild type under either sufficient or deficient Pi. Together, our study (i) identifies SNX1 as a key modulator of the plant response to low Pi and (ii) unravels its role in the modulation of PHT1;1 protein stability, PHT1;1 accumulation at the plasma membrane, and root Pi uptake. Significance Statement: High‐affinity phosphate (Pi) transporters (PHTs) PHT1;1 and PHT1;4 are necessary for plant root Pi uptake, but how their protein stability is modulated remains elusive. Our study (i) identifies Sorting Nexin1 as a key modulator of the plant response to low Pi and (ii) unravels its role in the modulation of PHT1;1 protein stability, PHT1;1 accumulation at the plasma membrane, and root Pi uptake.